HINDU CHARACTER EDUCATION AND ENTREPRENEURIAL ABILITY AS A CAPITAL OF INDEPENDENCE FOR ARTS AND CULTURE EDUCATION STUDENTS - Gunada, I Wayan Agus; Suastra, I Made (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The writing of the results of this study strengthens the understanding of the importance of Hindu character education and entrepreneurship for Hindu Religious Arts and Culture Education Study Program students. Art education students are formed into prospective educators, but more opportunities are needed for graduates to become educators. The lack of options, because the formation provided is sometimes lacking, so students must be able to read opportunities. Reading opportunities are part of financial literacy, so entrepreneurship needs to be integrated into lectures. Either through curriculum adaptation or entrepreneurial programs by universities. The assessment uses qualitative research, a type of literature study. Based on data analysis, Hindu character education is for students to develop prospective art educators who have attitudes and behaviours toward the teachings of Hinduism. The ability to be entrepreneurial, providing capital for art education students, to create the desire for entrepreneurship, as preparation for the future. This study aims to provide insightful reinforcement and benefits for art education students and can be a reference for relevant studies by academics and researchers.